Potensi Integrasi PMRI Berbantuan Augmented Reality untuk Meningkatkan Literasi Matematika: A Systematic Literature Review - Sakila Tunggal Dewi; Anna Fauziah; Sukasno (Proceeding of Silampari Conference of Life Science and Technology, 2026)
The low level of mathematical literacy achievement among Indonesian students highlights the need for pedagogical innovations supported by empirical evidence. This study aims to analyze the effectiveness of the Indonesian Realistic Mathematics Education (PMRI)/Realistic Mathematics Education (RME) approach, the characteristics of Augmented Reality (AR)-based learning media, and the integration patterns of both approaches in improving students' mathematical literacy. This research employed a Systematic Literature Review (SLR) method using the PRISMA protocol on 15 articles retrieved from Google Scholar and Sinta databases with the assistance of Publish or Perish, covering the period from 2017 to 2026. The data were analyzed thematically to identify research trends and patterns. The findings indicate that PMRI/RME has a positive impact on mathematical literacy, mathematical communication, mathematical connections, and problem-solving skills through contextual and meaningful learning experiences. AR-based learning media also demonstrate potential in enhancing conceptual understanding, spatial ability, and learning motivation through interactive three-dimensional visualization. However, no studies were found that comprehensively integrate PMRI, AR, and mathematical literacy assessment within a single research design. These findings suggest the need for further experimental studies on AR-assisted PMRI as an innovative learning approach to support the improvement of students' mathematical literacy.